NARSISME ORANG TUA DAN KESEHATAN MENTAL ANAK: ANALISIS MAQASHID SYARIAH - Julian Putri, Sinta Hapsari; Kumaini, Ruston (USRAH: Jurnal Hukum Keluarga Islam, 2025)
This study aims to examine the impact of parenting styles influenced by Narcissistic Personality Disorder (NPD) on children's mental health through the framework of maqashid sharia. Narcissistic parenting is often marked by excessive control, emotional manipulation, and a lack of empathy, all of which can lead to psychological disturbances in children. Using a qualitative approach, this study reveals that children raised by narcissistic parents are at risk of damage in their emotional, social, and cognitive development. this research promotes a more empathetic and constructive parenting model. Furthermore, muhasabah (self-reflection) is presented as a spiritual solution for parents with narcissistic tendencies, helping them to become more aware, responsible, and emotionally present caregivers. This study contributes to developing a parenting framework that aligns not only with psychological well-being but also with the ethical and spiritual values of Islam, aiming to preserve the overall well-being and moral integrity of children.